Western diet-induced visceral adipose tissue inflammation promotes Alzheimer’s disease pathology via microglial activation in a mouse model - Lim, Ji Sun; Kwak, Soyoung; Yu, Mi-Hee; Park, Mee-Na; Baek, Hye Suk; Kang, Junho; Hong, Jeong-Ho; Kim, Jin Kyung; Lee, Hye Won; Lee, Sang-Woo; Kim, Shin; Kim, Hae Won (Frontiers in Aging Neuroscience, 2025)
IntroductionWestern diet (WD)-induced visceral adipose tissue (VAT) inflammation is characterized by adipocyte hypertrophy, hypoxia, and apoptosis. Epididymal white adipose tissue (eWAT), a representative VAT depot in rodents, plays a central role in WD-induced inflammation by secreting pro-inflammatory cytokines that contribute to systemic and neuroinflammation. However, the mechanistic link between WD-driven eWAT inflammation and Alzheimer’s disease (AD) pathology remains unclear.MethodsWD feeding for 20 weeks was conducted to evaluate its effects on AD-related neuroinflammation and pathology in mice. Cerebral glucose metabolism was assessed using F-18 FDG-PET. RNA sequencing of eWAT and plasma cytokine profiling identified inflammation-associated factors. In vitro assays were performed to examine the effects of these cytokines on microglial activation, neuronal viability, and IL-6/STAT3 signaling.ResultsWD group exhibited significantly increased levels of neuroinflammatory markers and increased hippocampal levels of AD-related proteins including amyloid-beta oligomers, amyloid precursor protein, and phosphorylated tau. Additionally, F-18 FDG PET imaging revealed reduced glucose metabolism in the thalamus and hippocampus of WD group compared to controls. RNA sequencing of eWAT and cytokine profiling of plasma identified CCL8, CCL9, CXCL13, and IL-18 as significantly elevated pro-inflammatory cytokines. In vitro analyses demonstrated that these eWAT-associated cytokines directly activate microglial cells via the IL-6/STAT3 signaling pathway, promoting hippocampal neuronal death.DiscussionThese findings elucidate a critical pathway through which WD-induced eWAT inflammation exacerbates AD pathology through a systemic–to–neuroinflammation axis, highlighting the therapeutic potential of targeting eWAT-associated cytokines to mitigate diet-associated AD progression.